(untitled) (Scientific journal of the Fergana State University, 2025)
This article talks about the structural structure of the work “Qisasi Rabguziy”, which was considered one of the first agiographic works in eastern classical literature. This work, devoted to the history of the anbios” story of the Lord", differs sharply in its structure in other sources. The main reason for such differentiation lies in the creation of the work and the creative intention of the creator. In order to better understand the structural structure of the work, Alisher Navoi’s “Tarixi anbiyo va hukamo” is analyzed in a comparative aspect.